PENCITRAAN BUPATI DALAM PERSPEKTIF SEMIOTIKA BARTHES Analisis Penciitraan Bupati Sidoarjo Melalui Iklan Apartemen Royal Mutiara Residence pada Jawa Pos - Novianto, Tonny; Hamim, Hamim; Novaria, Rachmawati (Universitas 17 Agustus 1945 Surabaya, 2018)
Research starts from the interest of writer of the advertising world displayed through theprintable media especially Apartment Royal Mutiara Residence commercial in Jawa Pos, May 2015thedition. This commercial provides persuasive messages are presented in the textual message form andthe image message form. In this commercial there is a picture of Sidoarjo’s Regent H SaifulIllah,S.H.,M.Hum which is have a multi-interpretation in society as if this commercial have twoobjectives that mutually contrary, first, this commercial is intended to introduce the latest products ofApartment Royal Mutiara Residence, the second, this commercial also has a hidden meaning inconstructing image of Sidoarjo’s Regent H Saiful Illah, S.H.,M.Hum. This study adopted a qualitativeapproaches.. In this case, writers strove to unload the denotative meaning, connotative meaning andmyths which is found in verbal message and non verbal message that appear in the Apartment RoyalMutiara Residence commercial in Jawa Pos, May 2015th edition. From this research, can beconcluded that purport decker approach in Roland Barthes semiotic analysis, through connotativemeaning, denotative meaning and myths in this commercial, identified the explicit meaning ofpersuasive messages that appeare in this commercial aimed to construct the image of Sidoarjo’sregent H Saiful Illah, S.H., M.Hum to be much more positive in society.Keywords : Commercial, Semiotic, Image, Regent, Roland Barthes